Ambivalências nas relações entre poder e tecnologia em Black Mirror - Cardoso, Arzirio Alberto (2020)
The present work aims to analyze some episodes of the British television series Black Mirror, from the perspective of power relations. Taking as a starting point the idea that new forms of power relations are configured from the massive use of digital technological devices, such as cell phones and computers, we tried to examine, in the episodes “National Anthem” and “Nosedive”, how these new configurations are articulated in the fictional universe of the work. We tried to determine if, with the use of technological tools, there were attempts to break with vertical and horizontal forms of power, as well as if these attempts were successful or if, on the other hand, what happened was the maintenance of these relationships. To achieve these objectives, we used multiple critical, interpretive and analytical resources, always anchored in the comparison with the chosen theoretical bibliography. With this, we intend to demonstrate how this ambivalence is carried out, to unveil what it hides, to expose its fractures, its imbalances, to verify if the scale tilts to one side and, mainly, to demonstrate how the use of digital technology is the dominant strategy used by those who want the maintenance of power relations, as well as by those who aspire to its rupture.